PERCEPTION STUDENT OF DEPARTMENT GUIDANCE AND COUNSELING AT UNIVERSITAS MUHAMMADIYAH METRO INTO SCHOOL COUNSELOR PROFESSION - SERLI NOVITA SARI; NURUL ATIEKA (Universitas Muhammadiyah Metro, 2015)
Abstract: Guidance and Counseling Teaching profession is a profession with dignity and requiring scientific competence and qualifications. Many emerging negative perception, even from students of guidance and counseling to the profession of guidance and counseling. The problem in this research is formulated as follows: "What are the perceptions students of Guidance and Counselling, University of Muhammadiyah Metro the teaching profession Counseling?". The goal is to find out how students' perceptions of Guidance and Counselling, University of Muhammadiyah Metro the teaching profession Guidance and Counseling. The method used is quantitative descriptive. The population is students of guidance and counseling, the sample totaled 175 students. Instruments used in the form of Likert scale. The data analysis technique used percentages. The results showed that students' perceptions BK UM Metro is at a very high category to the teaching profession Guidance and Counseling. Suggestions put forward are: Based on these results, the researchers gave some suggestions are as follows: 1) for lecturers to add hours of practicum BK for students, and provide student guidance and counseling opportunities to interact more with teacher guidance and counseling directly in schools, and 2) the students are expected to apply to run a positive perception of the teaching profession Counseling well. Keywords: Perception, Student, Guidance and Counseling